2017
DOI: 10.20944/preprints201705.0073.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hochu-Ekki-to Treatment Improves Reproductive and Immune Modulation in the Stress-Induced Rat Model of Polycystic Ovarian Syndrome

Abstract: The traditional herbal medicine, Hochu-ekki-to, has been shown to have preventive effects on viral infection and stress. This study aimed to evaluate the clinical effects of Hochu-ekki-to on two stressrelated rat models of polycystic ovarian syndrome. Female Sprague-Dawley rats were divided into control and treatment groups, the latter of which were subjected to stress induced by exposure to adrenocorticotropic hormone (ACTH) or cold temperatures. After these stress inductions, rats were orally treated with di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The ability of estradiol to directly inhibit the secretion of FSH and LH via changes in mRNA levels and stimulate the increase in LHR mRNA expression has been reported [38, 39]. Previous studies indicated that the mRNA level of hormone receptors showed distinct differences with respect to external conditions [37, 40]. Thus, we measured the effect of cold exposure on the hormone receptors in the ovary and uterus.…”
Section: Discussionmentioning
confidence: 95%
“…The ability of estradiol to directly inhibit the secretion of FSH and LH via changes in mRNA levels and stimulate the increase in LHR mRNA expression has been reported [38, 39]. Previous studies indicated that the mRNA level of hormone receptors showed distinct differences with respect to external conditions [37, 40]. Thus, we measured the effect of cold exposure on the hormone receptors in the ovary and uterus.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that TJ-41 has immunomodulatory and anti-inflammatory effects in vitro and in vivo studies [14][15][16][17]. TJ-41 ameliorated ultraviolet-B-induced oxidative stress and skin dysfunction in hairless mice [18].…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 , 14 In infertility treatment, HET was demonstrated to improve the fertile competence in idiopathic male infertility and polycystic ovarian syndrome through immunomodulatory actions. 15 , 16 , 17 However, there is no study on the anti‐inflammatory effects of HET on aging females. Here, we sought to determine the potentials of HET treatment for infertility using an aging female animal model.…”
Section: Introductionmentioning
confidence: 99%
“…HET showed anti‐inflammatory effects on several chronic inflammatory conditions including aging 12–14 . In infertility treatment, HET was demonstrated to improve the fertile competence in idiopathic male infertility and polycystic ovarian syndrome through immunomodulatory actions 15–17 . However, there is no study on the anti‐inflammatory effects of HET on aging females.…”
Section: Introductionmentioning
confidence: 99%